Implementation of Progressive Motor Vehicle Tax Policy: A Source of Revenue For Accelerating Development - Hanum, Zahra Salsabilah; Siswoyo, Mukarto (Indonesian Journal of Advanced Research, 2024)
Local taxes are a vital income source for the West Java Provincial Government, including the Motor Vehicle Tax (PKB). This study examines the implementation of the progressive tax policy on motorized vehicles, regulated by West Java Regional Regulation Number 9 of 2023, as a means to reduce vehicle congestion in Cirebon City. Using a qualitative descriptive approach (normative-empirical), data was collected through interviews and observations. The findings indicate that while the policy implementation at the Cirebon City Samsat UPT is running well, it is not yet optimal. Influencing factors include effective communication, adequate resources, good staff disposition, and a structured bureaucracy. However, low taxpayer awareness and outdated tax data systems hinder policy optimization, requiring a collaborative and sustainable solution.